Semiotics and information design in the development of learning objects - Ferneda, Edberto [UNESP]; Dos Reis, Marcia Cristina [UNESP] (My University, 2019)
Learning objects are increasingly being used to subsidize teaching activities in face-to-face and distance learning courses. They are important for the educational context, since they allow the elaboration of new pedagogical strategies, facilitate the dissemination of knowledge, extend the scope of on-line education and are essential for the preservation and socialization of information. However, for this to happen, they must be developed in a standardized way, with an efficient user interaction interface that is understandable and can be retrieved in a fast and easy way. Such aspects can be better achieved by converging two important areas: Semiotics and Information Design. The first one focuses on the process of meaning (meaning generation) of the materials developed. The second, in turn, seeks to define premises to structure and organize information, with the purpose of optimizing the process of knowledge acquisition by the user. In this context, the present article aims to present the proposal of a proposal for a set of guidelines for the development of learning objects, based on the Semiotics and guidelines of Information Design. For this, exploratory and bibliographic research was adopted, based on relevant authors from the areas of Education and Information Science. As main results, the guidelines have been made available that can contribute to improving the quality of learning objects and, consequently, to facilitate their development process and encourage their use.
La semiótica y el diseño de la información en el desarrollo de objetos de aprendizaje
A semiótica e o design da informação no desenvolvimento de objetos de aprendizagem
Keywords: Educational technologies; Information design; Information science; Learning objects; Semiotics